Comparison of APACHE II and APACHE IV score as predictors of mortality in patients with septic shock in intensive care unit: A prospective observational study - Summit D Bloria; Rajeev Chauhan; Rashi Sarna; Satinder Gombar; Swati Jindal (Journal of Anaesthesiology Clinical Pharmacology, 2023)
Background and Aims: Prediction of outcome in intensive care unit (ICU) patients is of imperative importance. Our aim was to assess and compare the performance of Acute Physiology and Chronic Health Evaluation (APACHE) II and APACHE IV scores in predicting mortality in adult patients suffering from septic shock admitted to our ICU. Material and Methods: This was a prospective observational study conducted in a 14-bedded medical ICU of a tertiary care center from January 2019 to March 2020; 128 patients suffering from septic shock were included and APACHE II and IV scores were calculated. We also calculated the predicted and actual mortality rates and standardized mortality ratios. The receiver operating characteristic curves were used to assess discrimination. Results: Out of the 128 patients, 63 patients (49.21%) died. The mean (± standard deviation) admission APACHE II score was 16.7 ± 5.53, while the mean APACHE IV score was 67.25 ± 25.99. The non-survivors had significantly higher APACHE II and IV scores when compared to those who survived (P < 0.001). APACHE II had a slightly better discriminative power (with the area under the Receiver operating characteristic (ROC) curve of 0.78) than APACHE IV (with the area under the ROC curve of 0.74). The mean predicted mortality rate (PMR) of the patient population calculated on the basis of the APACHE II scoring system was 22.46 ± 15.76, and the mean PMR calculated as per the APACHE IV scoring system was 11.64 ± 15.59. Conclusion: Both APACHE II and APACHE IV underestimated mortality in septic shock patients. Both APACHE II and APACHE IV were comparable in differentiating survivors from non-survivors. However, there was a good correlation between the two models.